Therapeutic Argentine Tango Dancing for People with Mild Parkinson’s Disease: A Feasibility Study - Blandy, Laura M.; Beevers, Winifred A.; Fitzmaurice, Kerry; Morris, Meg E. (Frontiers in Neurology, 2015)
Background Individuals living with Parkinson’s disease (PD) can experience a range of movement disorders that affect mobility and balance and increase the risk of falls. Low health-related quality of life, depression, and anxiety are more common in people with PD than age-matched comparisons. Therapeutic dance is a form of physical activity believed to facilitate movement and therapy uptake. As well as being enjoyable, dancing is thought to improve mobility, balance, and well-being in some people living with PD. The primary objective of this study was to evaluate the feasibility and safety of a 4-week Argentine tango dance program for people with PD. Methods Six community dwelling individuals with mild to moderate PD were recruited from Parkinson’s support groups, movement disorder clinics, and the PD association in Australia. To minimize falls risk, participants were required to be <75 years of age and physically independent (Hoehn and Yahr stages I–III). They were also required to speak English. Participants attended a 1-hour dance class at a dance studio twice per week for 4 weeks. A professional dance instructor led and choreographed the Argentine tango dance classes. Physiotherapists were present to assist participants during the class and served as dance partners as necessary. The primary outcome was feasibility, which was determined by measures of recruitment, adherence, attrition, safety (falls, near misses and adverse events), and resource requirements. Secondary measures included the Beck Depression Inventory and the Euroqol-5D, administered at baseline and post intervention. Therapy outcomes pre- and post-intervention were analyzed descriptively as medians and interquartile ranges and using Wilcoxon matched pair signed-rank tests. Results The Argentine tango dance intervention was shown to be safe, with no adverse events. Adherence to the dance program was 89%. Depression scores improved after intervention (p = 0.04). Some challenges were associated with the need to quickly recruit participants and physiotherapists to act as dance partners during classes and to monitor participants. Conclusion The 4-week, twice weekly Argentine tango dancing program was shown to be feasible and safe for people with mild-to-moderately severe PD.